x² + bx - 81
there are 2 formula that fit this equation :
>> x² - a² = (x+a)(x-a)
or
>> x² + 2ax² + a² = (x+a)(x+a)
because the last value of our equation is negative value therefore we have to use the first formula >> x² - a² = (x+a)(x-a)
step:
x² + bx - 81
x² + bx - 9²
because we have to follow the first formula x² - a² therefore bx = 0
x² + bx - 9²
bx = 0
b = 0
Answer:
6.5 × 10¹¹
Step-by-step explanation:
I hope this helps you
Answer:
B
Step-by-step explanation:
Given
y = f(x), then
y = f(x ± a) is a horizontal translation of a units
• If f(x + a) then shift of a units left ←
• If f(x - a) then shift of a units right →
Answer: = ![2^{2}](https://tex.z-dn.net/?f=2%5E%7B2%7D)
Step-by-step explanation:
First, Combine Like Terms:
= 3x^2 + −5x^2 + 4x^2
=(3x^2+ −5x^2 + 4x^2)
=2x^2
* Hopefully this helps:) Mark me the brainliest:)!!
<em>~ 234483279c20~ </em>
Answer:
I miss the rage
Step-by-step explanation:
YAAAAAAAAAAAAAAAAAAAAAAA